Efficient and stable radiolabeling of polycyclic aromatic hydrocarbon assemblies: in vivo imaging of diesel exhaust particulates in mice. Issue 4 (26th November 2018) - Lee, Chang Heon; Shim, Ha Eun; Song, Lee; Moon, Hi Gyu; Lee, Kyuhong; Yang, Jung Eun; Song, Ha Yeon; Choi, Yong Jun; Choi, Dae Seong; Jeon, Jongho
Abstract : As a robust radioanalytical method for tracking carbonaceous particulates in vivo, polycyclic aromatic hydrocarbons from diesel exhaust were labeled with a radioactive-iodine-tagged pyrene analogue. Abstract : As a robust radioanalytical method for tracking carbonaceous particulates in vivo, polycyclic aromatic hydrocarbons from diesel exhaust were labeled with a radioactive-iodine-tagged pyrene analogue. Single-photon emission computed tomography and biodistribution studies showed high uptake and slow clearance of this matter in the respiratory system, which may underlie its severe toxicity.